(untitled) (Research, Society and Development, 2021)
Background: Patients with chronic kidney disease (CKD) often present with comorbidities like hypertension and diabetes. These conditions are often associated with loss of strength, which is a strong predictor of mortality. In this sense, it is reasonable to investigate genetic and physiological markers that could be related to strength and identify variables associated with this phenomenon. Objective: This study aimed to investigate the influence of angiotensin-1 converting enzyme (ACE) and angiotensinogen (AGT) M235T polymorphisms, and blood glucose on handgrip strength (HGS) for CKD patients with and without diabetes mellitus (DM). Methods: Male patients (n = 84) participated in this cross-sectional study. Patients were grouped based on the diagnosis of DM or not. We evaluated HGS using a dynamometer and ACE and AGT polymorphism by polymerase chain reaction. Results: There were differences in HGS between groups. Follow up analyses indicated a difference in the distribution of ACE polymorphism alleles was associated with the reduction in HGS in the DM group. The same response was present for AGT. A negative correlation existed between blood glucose levels and HGS (r = -0.334 with p < 0.05). Discussion: The present data suggests that there is a relationship between physical capacity and poor glycemic control. Conclusion: Our study demonstrated that blood glucose levels are associated with HGS in patients with CKD independent of ACE I/D and AGT M235T polymorphisms. Presence of DM may influence functional strength retention.